"Imperialism without imperialists" and the settler-colonial logics of reservation oolicing - Rocha Beardall, Theresa (Police and state crime in the Americas, 2024)
Growing awareness of U.S. police violence has sparked important discussions that link state violence and the nation’s settler-colonial origins, emphasizing the use of law enforcement to control racially marginalized groups. Yet, the enduring impact of settler-colonial logics of carcerality and elimination on the lives of Indigenous Peoples in the U.S., commonly known as American Indians under federal law, remains underexplored. This chapter examines how and why the social construction of the American Indian as othered, deviant, inherently criminal, and deserving of punishment within the criminal justice system and reservation policing is maintained. I argue that the U.S. deploys this “constructed criminality” as justification for ongoing land theft, racialized social hierarchies, physical and institutional violence, and other forms of othering that permeate U.S. carceral politics.